1989
DOI: 10.1038/bjc.1989.339
|View full text |Cite
|
Sign up to set email alerts
|

Role of the aclacinomycin A – doxorubicin association in reversal of doxorubicin resistance in K562 tumour cells

Abstract: Summary Acquired resistance to anthracyclines is characterised by a lower sensitivity to these agents, associated with impaired accumulation of drug. We have examined the ability of aclacinomycin A (ACM) associated with doxorubicin (DOX), to increase intranuclear DOX concentrations and, consequently, to enhance cytotoxic effects against drug resistant cells in vitro. A recently developed microspectrofluorometric technique is used to measure intranuclear DOX concentrations in sensitive and DOX-resistant K562 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…However, the intracellular anthracycline fluorescence does not accurately reflect the drug content because binding to DNA may cause quenching of the fluorescence, which is particularly pronounced for ACL (Skovsgaard, 1987; al., 1989). The fluorescence intensity of free ACL has been measured to be 200 times that of nucleus-bound drug (Millot et al, 1989). In the cytoplasm of the HB8065/S cells, and to a much lesser extent in the resistant HB8065/R cells, the anthracycline fluorescence appeared in numerous cytoplasmic vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intracellular anthracycline fluorescence does not accurately reflect the drug content because binding to DNA may cause quenching of the fluorescence, which is particularly pronounced for ACL (Skovsgaard, 1987; al., 1989). The fluorescence intensity of free ACL has been measured to be 200 times that of nucleus-bound drug (Millot et al, 1989). In the cytoplasm of the HB8065/S cells, and to a much lesser extent in the resistant HB8065/R cells, the anthracycline fluorescence appeared in numerous cytoplasmic vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the intracellular sequestration of weak bases and the enhanced outward transport should be distinct mechanisms. Indeed, it has been shown previously that the resistant K562-R cells present an enhanced doxorubicin efflux out of the nucleus compared with K562 cells (Millot et al 1989). However, we have determined that, for resistant cells, the efflux of AO was not enhanced (data not shown), although this molecule was intracellularly redistributed.…”
Section: Sequestration Models Of Weak Bases In Acidic Organelles Of Rmentioning
confidence: 99%
“…39 This affinity has also been reported on tumor cells using resonance Raman and surface-enhanced Raman scatescence of aclacinomycin A located in the nucleus is quenched 200 times upon binding to nuclear DNA. 31 Thus, tering microspectroscopies. 40,41 Knowing the potential target of DOX (Figure 1) in the cell by measuring absolute concentrations of nuclear anthracyclines, we were able to study the real drug transport.…”
Section: -29mentioning
confidence: 99%
“…46 DOX-resistant K562 cells overexstudy the relationship between the nuclear accumulation of DOX and the observed biological effects, the influence of press the P-glycoprotein responsible for active drug efflux. 31 For our purposes the comparison with DOX was very interestincubation temperatures on these processes was studied. Differentiation was assessed by the count of recruited hemoglobiing, because this analogue is taken up faster and to a higher extent by the cells, and shows reduced cross-resistance with nized cells after exposure to DOX at 37°C and 4°C.…”
Section: Corcorrelation Between Doxorubicin Nuclear Accumulation and mentioning
confidence: 99%
See 1 more Smart Citation